2022
DOI: 10.3390/agriculture12070985
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Changes in Crop Species Production Diversity in Mexico (1980–2020)

Abstract: Crop species diversity is a key component of agroecosystem resilience, food system stability, ecosystem services production, and sustainable development. Despite its importance, quantitative understanding of crop species diversity is often lacking. This study assesses changes in crop species production diversity in Mexico from 1980 to 2020 at state, regional, and national levels. Measures of crop species richness and effective diversity (alpha, beta, gamma) were derived from government production data on 304 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
0
6
0
1
Order By: Relevance
“…Irrigation intensity was found to be the strongest positive predictor of revenue stability in Models 1 and 2, which supports Hypothesis 2. The predicted positive association was based on studies highlighting the benefits of irrigation to crop production, productivity, and sustainability in Mexico [43,55,68,74], and other studies identifying a close association between irrigation and crop species diversity in Mexico [48,61]. As such, the findings of this study contribute to a growing list of irrigation benefits to crop productivity, sustainable development, and farming risk reduction in Mexico.…”
Section: Climate Instability Irrigation Intensity and Other Drivers O...mentioning
confidence: 52%
See 2 more Smart Citations
“…Irrigation intensity was found to be the strongest positive predictor of revenue stability in Models 1 and 2, which supports Hypothesis 2. The predicted positive association was based on studies highlighting the benefits of irrigation to crop production, productivity, and sustainability in Mexico [43,55,68,74], and other studies identifying a close association between irrigation and crop species diversity in Mexico [48,61]. As such, the findings of this study contribute to a growing list of irrigation benefits to crop productivity, sustainable development, and farming risk reduction in Mexico.…”
Section: Climate Instability Irrigation Intensity and Other Drivers O...mentioning
confidence: 52%
“…Crop species diversity was calculated from the SIAP crop production data. The harvested area (ha) of each crop species was used to calculate Shannon effective diversity, a commonly used index that combines richness and evenness diversity components into a measure of the effective number of crop species per equal area [48,49]:…”
Section: Crop Species Diversity (Independent)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although irrigated or industrial agriculture modality in Mexico covers four times less area than rainfed agriculture 47 , we find a strong correlation between increases in irrigated industrial agricultural area with respect to declines in the percent change in yield. Historical trends in agricultural land use indicate that irrigated industrial agriculture area has shown increases in most of the country, but specifically in the North of Mexico which has a strong impact on reducing honey bee colonies 47,48 . A possible explanation for the relationship between honey bee declines and the increases of both categories of agricultural land use, but particularly of irrigated industrial cropland, is attributable to agricultural expansion that, in turn, reduces natural habitats decreasing the availability of floral resources in natural areas and increasing nutritional deficits 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The diversification of exports and export markets has proven to be a successful approach for several countries, especially in the context of fruit exports (LaFevor, 2022). This diversification process can be an effective strategy for developing countries to advance their economic development and reduce their dependence on a limited number of products or markets (Vázquez, 2016).…”
Section: Introductionmentioning
confidence: 99%

Diversification of Fresh Asparagus Exports from Perú

Arbulú Ballesteros,
Montes Ninaquispe,
Ludeña Jugo
et al. 2024
JESR